Implementation of double mini-beta optics at the diamond light source - Singh, B; Fielder, R; Martin, I; Rehm, G; Bartolini, R (2011)
We report the results of the implementation of two vertical mini-beta and horizontally focussing optics at the Diamond light source, the first in August 2010 and the second in March 2011. Commissioning results of the two optics changes and the experimental characterization of the optics are compared with the expected performance and theoretical modelling. The implications of a possible third customised optics are also investigated. Copyright © 2011 by IPAC'11/EPS-AG.